Veno-Arterial Extracorporeal Membrane Oxygenation in Elective High-Risk Percutaneous Coronary Interventions - Bai, Ming; Lu, Andong; Pan, Chenliang; Hu, Sixiong; Qu, Wenjing; Zhao, Jing; Zhang, Bo (Frontiers in Medicine, 2022)
Background The safety and feasibility of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) as mechanical circulatory support in high-risk percutaneous coronary intervention (HR-PCI) remain unclear. Methods This retrospective study included patients with complex and high-risk coronary artery disease who underwent elective PCI with VA-ECMO support pre-operatively during March 2019–December 2020. Rates of VA-ECMO-related complications, complications during PCI, death, myocardial infarction, and stroke during hospitalisation and 1-year post-operatively were analysed. Results Overall, 36 patients (average age: 63.6 ± 8.9 years) underwent PCI. The average duration of VA-ECMO support was 12.5 (range, 3.0–26.3) h. Intra-aortic balloon pump counterpulsation was used in 44.4% of patients. The SYNTAX score was 34.6 ± 8.4 pre-operatively and 10.8 ± 8.8 post-operatively (P < 0.001). Intraoperative complications included pericardial tamponade (N = 2, 5.6%), acute left-sided heart failure (N = 1, 2.8%), malignant arrhythmia requiring electrocardioversion (N = 2, 5.6%), and no deaths. Blood haemoglobin levels before PCI and 24 h after VA-ECMO withdrawal were 145.4 ± 20.2 g/L and 105.7 ± 21.7 g/L, respectively (P < 0.001). Outcomes during hospitalisation included death (N = 1, 2.8%), stroke (N = 1, 2.8%), lower limb ischaemia (N = 2, 5.6%), lower limb deep venous thrombosis (N = 1, 2.8%), cannulation site haematoma (N = 2, 5.6%), acute renal injury (N = 2, 5.6%), bacteraemia (N = 2, 5.6%), bleeding requiring blood transfusion (N = 5, 13.9%), and no recurrent myocardial infarctions. Within 1 year post-operatively, two patients (5.6%) were hospitalised for heart failure. Conclusions Veno-arterial extracorporeal membrane oxygenation mechanical circulation support during HR-PCI is a safe and feasible strategy for achieving revascularisation in complex and high-risk coronary artery lesions. VA-ECMO-related complications require special attention.